Evaluating hotel advertisements efficiency using data envelopment analysis - Hadad, Yossi; Friedman, Lea; Israeli, Aviad A. (Journal of Business Economics and Management, 2004)
This paper introduces popular methods for ranking alternatives with multiple inputs and multiple outputs in the DEA context. The ranking methods are based on different criteria. Consequently, the ranking of the alternatives are not always the same, particularly as regards the best alternative. The decision maker, however, must make an absolute decision as to the most favored alternative. This study proposes a new ranking method, which is based on the average of the highly correlated ranking method. The new method is applied on a case study of ranking hotels in Israel.First Published Online: 14 Oct 2010